2012
DOI: 10.1007/s10545-012-9494-x
|View full text |Cite
|
Sign up to set email alerts
|

Creatine metabolism in urea cycle defects

Abstract: Creatine (Cr) and phosphocreatine play an essential role in energy storage and transmission. Maintenance of creatine pool is provided by the diet and by de novo synthesis, which utilizes arginine, glycine and s-adenosylmethionine as substrates. Three primary Cr deficiencies exists: arginine:glycine amidinotransferase deficiency, guanidinoacetate methyltransferase deficiency and the defect of Cr transporter SLC6A8. Secondary Cr deficiency is characteristic of ornithine-aminotransferase deficiency, whereas non-u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 43 publications
2
29
0
Order By: Relevance
“…As the liver extracts only a small quantity of citrulline, this aminoacid is mainly transported to the kidney and metabolized to arginine in the tubules of the cortical zone and used for guanidino acetate synthesis by arginine-glycine amidotransferase (AGAT), the first step of creatine synthesis, with ornithine as by-product [73]. In ORC1 deficiency, the high cytosolic ornithine concentrations inhibit AGAT leading to secondary creatine deficiency [21,44,74]. Secondary creatine deficiency may be also due to low cellular arginine availability due to the block in UC flow.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the liver extracts only a small quantity of citrulline, this aminoacid is mainly transported to the kidney and metabolized to arginine in the tubules of the cortical zone and used for guanidino acetate synthesis by arginine-glycine amidotransferase (AGAT), the first step of creatine synthesis, with ornithine as by-product [73]. In ORC1 deficiency, the high cytosolic ornithine concentrations inhibit AGAT leading to secondary creatine deficiency [21,44,74]. Secondary creatine deficiency may be also due to low cellular arginine availability due to the block in UC flow.…”
Section: Resultsmentioning
confidence: 99%
“…Protein restriction may be combined with sodium benzoate or sodium phenylbutyrate. If plasma creatine levels are low, creatine supplementation should be instituted [1,44,74]. Citrulline supplementation has been shown to allow better metabolic control and to avoid secondary creatine deficiency [21].…”
Section: Resultsmentioning
confidence: 99%
“…33 Guanidinoacetate can be elevated in patients with urea cycle defects such as arginase deficiency, although creatine concentrations tend to be normal or mildly elevated in this situation. 69,70 While not a CDS indicator, it is worth noting that elevated creatine in plasma has been suggested as a potential biomarker for mitochondrial disorders. 71,72 In general, the use of creatinine as a biomarker for the diagnosis of CDSs (aside from the creatine-to-creatinine ratio for CRTR deficiency) is of limited value.…”
Section: Discussionmentioning
confidence: 99%
“…However, van Spronsen et al (2006) showed borderline low brain Cr levels in patients with ASS deficiency. Moreover, Boenzi et al (2012) in a study with 32 patients observed differences in the Cr levels after treatment with arginine, being elevated in ASL and lysinuric protein intolerance (LPI, MIM#222700) and reduced in OTC, ASS, and HHH, revealing that the response depends on the arginine availability, although GAA levels were normalized in most of the patients.…”
Section: Aslmentioning
confidence: 98%
“…One of the consequences of the urea cycle defects (UCDs), except for arginase deficiency, is the low levels of arginine that could lead to a decreased Cr synthesis. In fact, some authors showed that GAA and Cr were low in plasma and urine in patients with UCDs (Arias et al 2004;Boenzi et al 2012). These disorders included argininosuccinate synthetase deficiency (ASS, MIM#215700), argininosuccinate lyase deficiency (ASL, MIM#207900), ornithine transcarbamylase deficiency (OTC; MIM#311250), and hyperammonemia-hyperornithinemia-homocitrullinuria syndrome (HHH; MIM#238970).…”
Section: Creatine In Congenital Urea Cycle Disordersmentioning
confidence: 99%